2021
DOI: 10.1186/s12986-021-00573-0
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced prediabetes: effects of exercise treatment on risk factors for cardiovascular complications

Abstract: Background An animal model of prediabetes that has been developed in our laboratory using a high fat high carbohydrate diet and lack of physical activity displays risk factors for cardiovascular complications. The effect of exercise against these risk factors in this animal model remains unknown. Therefore, we evaluated the effect of intermittent and regular exercise treatment on the risk factors for cardiovascular complications in this animal model of prediabetes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…In contrast to long-term chronic hyperglycaemia, acute blood glucose fluctuations can induce oxidative stress, increasing monocyte adhesion to endothelial cells, increasing endothelial cell apoptosis and exacerbating vascular injury [ 152 ]. In contrast, regular or intermittent exercise improves oxidative stress biomarkers and delays or prevents the development of prediabetes into diabetes [ 153 , 154 ]. In diabetic mice, four weeks of exercise was shown to reduce ERS and oxidative stress by inducing AMPK-PPARδ activation, increasing NO bioavailability in endothelial cells and vascular tissue, improving vascular endothelial function, and providing a potentially effective target for the treatment of diabetic vasculopathy [ 155 ].…”
Section: Effect Of Targeting Oxidative Stress In Diabetes-induced End...mentioning
confidence: 99%
“…In contrast to long-term chronic hyperglycaemia, acute blood glucose fluctuations can induce oxidative stress, increasing monocyte adhesion to endothelial cells, increasing endothelial cell apoptosis and exacerbating vascular injury [ 152 ]. In contrast, regular or intermittent exercise improves oxidative stress biomarkers and delays or prevents the development of prediabetes into diabetes [ 153 , 154 ]. In diabetic mice, four weeks of exercise was shown to reduce ERS and oxidative stress by inducing AMPK-PPARδ activation, increasing NO bioavailability in endothelial cells and vascular tissue, improving vascular endothelial function, and providing a potentially effective target for the treatment of diabetic vasculopathy [ 155 ].…”
Section: Effect Of Targeting Oxidative Stress In Diabetes-induced End...mentioning
confidence: 99%
“…Our laboratory has established a pre-diabetic rat model that mimics the human condition. Using this model, we investigated changes in the activity of the cardiovascular system, the functioning of organs such as the kidney and liver, and physiological systems such as renin-angiotensin-aldosterone system in the pre-diabetic state 85–88. The HPA axis and immune systems have also been observed in the pre-diabetic state 89 90.…”
Section: Pre-diabetes: Can Moderate Hyperglycemia Have the Same Effec...mentioning
confidence: 99%
“…Using this model, we investigated changes in the activity of the cardiovascular system, the functioning of organs such as the kidney and liver, and physiological systems such as renin-angiotensin-aldosterone system in the prediabetic state. [85][86][87][88] The HPA axis and immune systems have also been observed in the pre-diabetic state. 89 90 In a study by Mosili and colleagues, hyperactivity of the HPA axis was observed in the pre-diabetic state.…”
Section: Effects Of Immune System Dysregulation Due To Hyperglycemia ...mentioning
confidence: 99%
“…Reduced (NO) levels were observed in (T2D) patients, which is in agreement with the results reported in a previous study 57,63 . Overproduction of (NO) is associated with various inflammatory conditions, including diabetes [64][65][66][67][68] . The results of this study show a decrease in plasma triglyceride and LDL-C levels and an increase in HDL-C levels.…”
Section: Oxidative Stress Biomarkersmentioning
confidence: 99%